Vitamin D status and physical performance, muscular strength and mass in older adults with sarcopenia - M. A. Hordina; V. F. Orlovskyi; A. V. Zharkova; T. M. Rudenko; D. V. Levchenko (Zaporožskij Medicinskij Žurnal)
The purpose of the study: to assess the level of vitamin D in older adults (age ≥60 years) with sarcopenia. To analyze the relationship between concentration of 25(OH)D and muscular strength, muscle mass, physical activity and markers of low grade inflammation in patients with sarcopenia.